Proceedings of the 2012 ACM/IEEE International Symposium on Low Power Electronics and Design 2012
DOI: 10.1145/2333660.2333688
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic reconfiguration of photovoltaic energy harvesting system in hybrid electric vehicles

Abstract: Photovoltaic (PV) energy harvesting system is a promising energy source for battery replenishment in hybrid electric vehicles (HEVs.) The PV cell array is installed on different parts of a vehicle body such as the engine hood, door panels, and the roof panel. Non-uniformity of the solar irradiance and temperature on the PV cell array is, however, a serious obstacle to efficient utilization of the PV system in HEVs because such variation, if not managed properly, can result in a significant degradation in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Besides that, the embedded computing system will also generate and send the reset and clock signal to all APS switches present in the reconfigurable PV module. Over the years, many different kinds of embedded systems are used, such as computers, 32,33,37 field programmable gate array, 38,39 and Raspberry PI. 42 Algorithm.…”
Section: Photovoltaics Embedded With Cmos Switchesmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides that, the embedded computing system will also generate and send the reset and clock signal to all APS switches present in the reconfigurable PV module. Over the years, many different kinds of embedded systems are used, such as computers, 32,33,37 field programmable gate array, 38,39 and Raspberry PI. 42 Algorithm.…”
Section: Photovoltaics Embedded With Cmos Switchesmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31] A PV module embedded with complementary metal oxide semiconductor (CMOS) switches has recently been proposed as an alternative to the SP-based PV module with bypass diode. [32][33][34][35][36][37][38][39] Studies have shown that PV modules embedded with switches have better capability for dealing with partial shading, mismatch issues, and faulty conditions. 32,33,35,37 Additionally, such PV modules reconfigure in real-time (i.e., an number of PV cells connected in series × number of cells connected in parallel change), which enables creating a power island.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference work [6,7] suggested dynamic PV array reconfiguration to combat partial shading. The proposed reconfiguration technique can make both the shaded and lighted PV cells work at or close to their MPPs simultaneously, thereby improving the PV system output power.…”
Section: Reconfiguration Structurementioning
confidence: 99%
“…This paper introduces a fast PV cell array reconfiguration for the partial solar powered EV. We borrow the dynamic PV module reconfiguration architecture from previous work [6,7,8]. However, the solar irradiance levels are rapidly changing in the case of PV modules on the vehicle due to nearby shading and direction changes.…”
Section: Introductionmentioning
confidence: 99%